PENERAPAN AKUNTANSI PENJUALAN ANGSURAN DAN PERLAKUAN BARANG YANG DITARIK KEMBALI PADA PT. KAISAR MOTOR JAYA BATAM - Elmi E; Ravika Permata Hati; Hamidi Hamidi (Universitas Riau Kepulauan, 2015)
Revenues is one important element in preparing the income statemen, because the amount of income and expense recognized in the accounting period will affect the amount of income that will be recognized by the company. Profits derived from the revenue after deducting the expenses incurred in the activities of the company The study was conducted at PT. Kaisar Motor Jaya Batam, as one private company engaged in the sale of trimotorcycles. The company’s revenue earned from the sale of the motor. This study aims to determine how the accounting treatment of revenues and expenses to the company’s earnings, whether itisinaccordance with financial accounting standars. The results showed that the company has aplplied the method of revenue recognition under PSAK No. 23